1986
DOI: 10.2307/1444996
|View full text |Cite
|
Sign up to set email alerts
|

Resource Partitioning in Fish Assemblages: A Review of Field Studies

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. American Society of Ichthyologists and Herpetologists (ASIH)is collaborating with JSTOR to digitize, preserve and extend access to Copeia.In this study I review the literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
585
3
36

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 746 publications
(642 citation statements)
references
References 126 publications
18
585
3
36
Order By: Relevance
“…Population density, survival, secondary production and individual growth should respond to gradients in habitat quality (Chatry et al 1983, Baltz et al 1998. In this study, we found that patterns of microhabitat use among and within species differed substantially and often statistically, and suggested strong resource partitioning (Ross 1986). Overlaps in resource use were generally low (0 = 0.24, range = 0.01 to 0.59), especially between closely related species, where proportional overlap ranged from 0.19 to 0.38.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Population density, survival, secondary production and individual growth should respond to gradients in habitat quality (Chatry et al 1983, Baltz et al 1998. In this study, we found that patterns of microhabitat use among and within species differed substantially and often statistically, and suggested strong resource partitioning (Ross 1986). Overlaps in resource use were generally low (0 = 0.24, range = 0.01 to 0.59), especially between closely related species, where proportional overlap ranged from 0.19 to 0.38.…”
Section: Discussionmentioning
confidence: 69%
“…Overlaps in resource use were generally low (0 = 0.24, range = 0.01 to 0.59), especially between closely related species, where proportional overlap ranged from 0.19 to 0.38. Ecological segregation (Ross 1986) appeared to be general throughout the assemblage with the species assemblage structure changing along temporal, spatial and physico-chemical gradients in the factor analysis of microhabitat use (Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Casatti et al 2005, Balassa et al 2004, Santos et al 2011). Resource partitioning is considered the principal factor in structuring the aquatic communities (Ross 1986). Hence, the coexistence of the species can be favored by ecomorphological differences.…”
Section: Discussionmentioning
confidence: 99%
“…spatial variation. Resource partitioning, defined as any considerable difference in the use of resources among species, like differences in diet or in temporal and spatial use of the habitat (Ross 1986), constitutes an important mechanism allowing the species coexistence. When the alimentary resources are available in abundance, they can be shared among species; on the other hand, when they are scarce, there is segregation among species through ontogenetic changes in the diet and/or differences in spatial/temporal distribution (Arcifa et al 1991).…”
Section: Consumedmentioning
confidence: 99%